Measurement of Erect and Supine Waist Circumference among Healthy Adults - Ghimire, Pukar; Gajurel, Bikram Prasad; B.K., Kanshi Ram; Duwal, Gajendra (Journal of National Heart and Lung Society Nepal, 2023)
Background: Erect waist circumference is a key marker of obesity. However, it is not possible to measure erect waist circumference in all patients. This study aims to formulate an equation to calculate erect waist circumference from supine waist circumference for both males and females in our population. Methods: Thirty female and thirty male volunteers were recruited. Erect and supine waist circumference measurements were taken as per WHO STEPS protocol. The measurements were made at the approximate midpoint between the lower margin of the last palpable rib and the top of the iliac crest at the end of a normal expiration. Results: Erect waist circumference was found to be greater than supine waist circumference with the mean difference in overall participants being 2.6 + 1.4 cm. The difference between erect and supine waist circumference was significantly higher in females (Mean difference 3.1 + 1.6 cm) than in males (Mean difference 2.2 + 0.9 cm). A simple correction formula was derived as corrected erect waist circumference = -2.757 + 0.9 x Gender + 1.048 x Supine waist circumference. Conclusion: This formula which has been derived can be used in situations where only supine waist circumference measurement is possible.